2017
DOI: 10.2460/javma.251.11.1313
|View full text |Cite
|
Sign up to set email alerts
|

Urethral diverticulum and urolithiasis in a female guinea pig (Cavia porcellus)

Abstract: CASE DESCRIPTION A 5-year-old sexually intact female guinea pig was evaluated because of mild dysuria and a subcutaneous mass located cranioventral to the urogenital openings. CLINICAL FINDINGS Non-contrast-enhanced CT and surgical exploration of the distal aspect of the urethra revealed a urethral diverticulum with an intraluminal urolith. Analysis revealed that the urolith was composed of calcium carbonate and struvite. TREATMENT AND OUTCOME The urolith was surgically removed and ablation of the urethral div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…While CT imaging is not as commonly employed in small mammals like guinea pigs compared to dogs and cats, its utility extends to various clinical scenarios due to its inherent cross-sectional nature, which mitigates the superimposition of anatomical structures. Indications include evaluation of dental disease and other bony structures of the head ( Krautwald-Junghanns et al , 2011 ) or assessment of the thoracic and abdominal cavities for anatomical and medical purposes ( Parkinson et al , 2017 ; Zehtabvar et al , 2023 ). Furthermore, the injection of intravenous contrast medium enhances the vascular structures of the body and allows the evaluation of potential vascular malformations.…”
Section: Discussionmentioning
confidence: 99%
“…While CT imaging is not as commonly employed in small mammals like guinea pigs compared to dogs and cats, its utility extends to various clinical scenarios due to its inherent cross-sectional nature, which mitigates the superimposition of anatomical structures. Indications include evaluation of dental disease and other bony structures of the head ( Krautwald-Junghanns et al , 2011 ) or assessment of the thoracic and abdominal cavities for anatomical and medical purposes ( Parkinson et al , 2017 ; Zehtabvar et al , 2023 ). Furthermore, the injection of intravenous contrast medium enhances the vascular structures of the body and allows the evaluation of potential vascular malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Carotenuto, DVM, and A.S.Edell, MLAS, DVM, unpublished data, 2021. 17 Encouraging water consumption by guinea pigs is often promoted to maintain diuresis to minimize calcium salt deposition and subsequent urolith formation. 18 In a previous study, 6 it was shown that guinea pigs prefer drinking from a bottle drinker.…”
Section: S99mentioning
confidence: 99%